The west side of any mountain : place, space, and ecopoetry - Bryson, J. Scott, 1968- (University of Iowa Press, 2005)
In contrast to nature poets of the past who tended more toward the bucolic and pastoral, many contemporary nature poets are taking up radical environmental and ecological themes. In the last few years, interesting and evocative work that examines this poetry has begun to lay the foundation for studies in ecopoetics. Informed in general by current thinking in environmental theory and specifically by the work of cultural geographer Yi-Fu Tuan, The West Side of Any Mountain participates in and furthers this scholarly attention by offering an overarching theoretical framework with which to approac.